Sustainability reporting assurance and corporate employment structure: empirical evidence from Chinese listed companies - Hanlu Cheng; Sifan Gao (Humanities & Social Sciences Communications)
Abstract As an external governance mechanism designed to enhance the credibility of reports, the impact of sustainability reporting assurance (SRA) on corporate employment decisions warrants close examination. This paper systematically investigates the influence and mechanisms of SRA on corporate employment structure, utilizing data from the sustainability reports and assurance reports of Chinese A-share listed companies from 2010 to 2022. The study finds that SRA significantly affects corporate employment structure, manifested by an increase in the proportion of high-skilled employees and a decrease in that of low-skilled employees. Moreover, this effect is more pronounced when the assurance is provided by accounting firms. Mechanism analysis reveals that enhancing corporate reputation and increasing investment in on-the-job training are the main channels through which SRA affects corporate employment structure. Heterogeneity analysis indicates that the impact of SRA on corporate employment structure is more pronounced in industries with high social responsibility sensitivity and enterprises with high labor dependency. This study not only uncovers the microeconomic consequences and intrinsic mechanisms of SRA on corporate employment structure for the first time but also enriches the literature on the driving factors of employment structure at the corporate level.